The relationship of real estate between foreign direct investment, gross domestic product, interest rate and inflation rate in Malaysia / Nurul ‘Izzati Abd Latif - Abd Latif, Nurul ‘Izzati (2013)
The real estate investment and development offers bright prospects for Asia, including Malaysia. The real estate players were now focusing on Asia following the economic problems in the US and debt crisis in Europe. This is because they were attracted by Asia’s steady growth in gross domestic product. However, the real estate segment accounted for about 60 per cent of an economy of each country. The problem of forecasting the movement of real estate rates attracts increasing attentions. Primarily, the impact of the financial crisis on US and Europe were huge. Thereby, it would be attentiveness to ascertain the factors of real estate volatility in Malaysia. According to A. Chaney and M. Hoesli(2010) their research believe that a change in interest rates made real estate to be less sensitive than any asset with the same average nominal growth rate of cash flows. However, the major determinants of the interest rate sensitivity are the property’s remaining lifetime, the risk premium, the state of the macroeconomic environment and the degree of rotation of the interest rate curve. Furthermore, research from R. Edelstein(2011) shows that if the quality of the legal system and corporate governance improves, the excess risk adjusted rates of return decline. The demonstrates empirically that legal and governance quality are statistically significant determinants of excess rates of return for publicly traded real estate companies for 20 countries during 2004-2006. On the other hand, Zhou. X and Clements. S (2010) prove that there was significant implications for not only Chinese homeowners but investors worldwide for the inflationhedging ability. Generally, the knowledge of the Chinese market’s inflation-hedging ability with the return and risks is very important for international investors looking to improve their investment portfolio. Thus, K.M. Wang (2010) agreed that real estate returns in Taipei City, Taichung City and Taiwan region cannot hedge unexpected inflation. As the results, the metropolitan areas have a negative impact while in Taipei city has a positive impact on returns. The study of C. He (2011) found that provinces with relatively developed land and housing markets and provinces in which local governments preserve those markets attracted by foreign investors in real estate industry. Meanwhile, strong law enforcement and good local governance favourable to foreign direct investment and real estate. However, according to Vishwakarma, V.K and French, J.J (2010), they find that there is a statistically significant break in the relationship between macro variables and Indian real estate market in March of 2000, corresponding to the period when the Indian government was relaxing restrictions on foreign FDI investment. The study of Fung. G.H (2010) surveyed that there are housing affordability problem caused of faster rising housing cost even though GDP and income levels have been growing rapidly. Hence, the key factor in China’s economic growth and an essential part of the overall functioning of the economy are real estate development.